Neuroleptics as a cause of painful legs and moving toes syndrome. (22nd December 2014) - Azzi, Jacques; Atweh, Samir; Saade, Nayef; Jabbour, Rosette
Abstract : Painful legs and moving toes syndrome is rare. It is predominantly diagnosed in middle-aged adults following a history of spinal cord surgery or trauma. The syndrome consists of abnormal repetitive movements, most commonly in the lower extremities, accompanied by pain in the affected limb. Pain usually precedes the movements. We report a case in a young patient that we believe was induced by the intake of a low-potency neuroleptic, which was prescribed to him for anxiety. The patient was treated with carbamazepine with mild relief of pain and later on with botulinum injection, which significantly reduced the movements and mildly improved the pain. After stopping the treatment, the beneficial effect lasted for about 3 months after which his condition gradually returned to its initial state.